2 μm emission properties and nonresonant energy transfer of Er(3+) and Ho(3+) codoped silicate glasses - Cao, Ruijie (Sci Rep, 2016)
2.0 μm emission properties of Er(3+)/Ho(3+) codoped silicate glasses were investigated pumped by 980 nm LD. Absorption spectra were determined. Intense mid-infrared emissions near 2 μm are observed. The spectral components of the 2 μm fluorescence band were analyzed and an equivalent model of four-level system was proposed to describe broadband 2 μm emission. Low OH(−) absorption coefficient (0.23 cm(−1)), high fluorescence lifetime (2.95 ms) and large emission cross section (5.61 × 10(−21) cm(2)) corresponding to Ho(3+): (5)I(7)→(5)I(8) transition were obtained from the prepared glass. Additionally, energy transfer efficiency from the Er(3+): (4)I(13/2) to the Ho(3+): (5)I(7) level can reach as high as 85.9% at 0.75 mol% Ho(2)O(3) doping concentration. Energy transfer microscopic parameters (C(DA)) via the host-assisted spectral overlap function were also calculated to elucidate the observed 2 μm emissions in detail. Moreover, the rate equation model between Er(3+) and Ho(3+) ions was developed to elucidate 2 μm fluorescence behaviors with the change of Ho(3+) concentration. All results reveal that Er(3+)/Ho(3+) codoped silicate glass is a promising material for improving the Ho(3+) 2.0 μm fiber laser performance.